Defining mtDNA origins and population stratification in Rio de Janeiro. (May 2018) - Simão, Filipa; Ferreira, Ana Paula; de Carvalho, Elizeu Fagundes; Parson, Walther; Gusmão, Leonor
Highlights: Population data (n = 205) are reported for the mtDNA control region in samples from Rio de Janeiro (Brazil). High haplotype diversity is present as a result of significant African, European and Native American contributions. The main maternal gene pool can be traced to Africa, arriving mainly from the Atlantic Coast region. A comparison between mtDNA and autosomal data revealed population substructure. The observed population substructure has to be considered in forensic analysis. Abstract: The genetic composition of the Brazilian population was shaped by interethnic admixture between autochthonous Native Americans, Europeans settlers and African slaves. This structure, characteristic of most American populations, implies the need for large population forensic databases to capture the high diversity that is usually associated with admixed populations. In the present work, we sequenced the control region of mitochondrial DNA from 205 non-related individuals living in the Rio de Janeiro metropolitan region. Overall high haplotype diversity (0.9994 ± 0.0006) was observed, and pairwise comparisons showed a high proportion of haplotype pairs with more than one-point differences. When ignoring homopolymeric tracts, pairwise comparisons showed no differences 0.18% of the time, and differences in a single position were found with a frequency of 0.32%. A high percentage of African mtDNA was found (42%), with lineages showing a major South West origin. For the West Eurasian and Native American haplogroups (representing 32% and 26%, respectively) it was not possible to evaluate a clear geographic or linguistic affiliation. When grouping the mtDNA lineages according to their continental origin (Native American, European and African), differences were observed for the ancestry proportions estimated with autosomal ancestry-informative markers, suggesting some level of genetic substructure. The results from this study are in accordance with historical data where admixture processes are confirmed with a strong maternal contribution of African maternal ancestry and a relevant contribution of Native American maternal ancestry. Moreover, the evidence for some degree of association between mtDNA and autosomal information should be considered when combining these types of markers in forensic analysis.